Interests, identity, and the geopolitical causes for military rule in Egypt. - Lamon, William (AUC Knowledge Fountain, 2015)
"Interests, Identity, and the Geopolitical Causes for Military Rule in Egypt." The thesis is an examination of the geopolitics of Egypt, from the Free Officers revolution in 1952, up to the present. The work analyzes the evolution of Egypt's political and economic infrastructure as subsequent military regimes simultaneously pursued state interests and managed internal discontent associated with regional identities. In the work, "identity" refers to ethnic, tribal, and religious affiliations present within populations throughout the Middle East. A population’s loyalty and identification with an alternative community complicates security dynamics in the region, as they undermine the legitimacy of governments and ignore the sovereign boundaries of states. While Egypt remains strategically valuable to many external states with interests in the region, other geopolitical realities make their economic and security interests heavily reliant upon the aid that they derive from international relationships. Since 1952, the military establishment's response to the dual demands of interests and identities allowed them to maneuver into a position of influence and oversight within the political and economic infrastructure of the state. They also became an intricate part of international partnerships and institutions, reinforcing external state interests in the stability and survival of the military regime. The thesis describes how the military regime was able to navigate recent political turmoil, maintain their international relationships, and eliminate influential political rivals. In doing so, the military establishment displayed their own stability as an institution, as well as a level of political, diplomatic, and military competence. Domestically, the popularity of Egypt's new President, Abdel Fattah el-Sisi, suggests that the military has reaffirmed their legitimacy as an institution and governing body. Of course, it is possible that a democratic political system could eventually emerge in Egypt. For the time being, Egypt no longer has an influential political entity capable of challenging the military establishment, and external actors continue to provide aid in order to stabilize the current regime. As a result, the work concludes that the military establishment is likely to maintain their political and economic influence over the Egyptian state for the foreseeable future.